2017
DOI: 10.1161/circulationaha.116.024143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Prediction of Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) is common and has a substantial genetic basis. Identification of individuals at greatest AF risk could minimize the incidence of cardioembolic stroke. Methods To determine whether genetic data can stratify risk for development of AF, we examined associations between AF genetic risk scores and incident AF in five prospective studies comprising 18,919 individuals of European ancestry. We examined associations between AF genetic risk scores and ischemic stroke in a separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 49 publications
1
76
1
Order By: Relevance
“…37 In contrast, our comprehensive AF definition included self-report, ICD9 and ICD10 codes, and AF-related procedures such as catheter ablation, which likely minimized misclassification of AF cases as referents. Genetic risk for AF has previously been associated with a variety of clinical outcomes including incident AF, 38, 39 ischemic stroke, 39, 40 and variably with catheter ablation success, 41 though any potential clinical application of genetic risk information may be highly context-dependent. Whether the magnitude of AF risk explained by genome-wide variation, or perhaps family history of AF, will contribute meaningfully to clinical risk assessment warrants further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…37 In contrast, our comprehensive AF definition included self-report, ICD9 and ICD10 codes, and AF-related procedures such as catheter ablation, which likely minimized misclassification of AF cases as referents. Genetic risk for AF has previously been associated with a variety of clinical outcomes including incident AF, 38, 39 ischemic stroke, 39, 40 and variably with catheter ablation success, 41 though any potential clinical application of genetic risk information may be highly context-dependent. Whether the magnitude of AF risk explained by genome-wide variation, or perhaps family history of AF, will contribute meaningfully to clinical risk assessment warrants further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a separate sample, we observed that AF genetic risk was associated with cardioembolic stroke even in the absence of clinically recognised AF (figure 3). 32 …”
Section: Potential Clinical Applicationsmentioning
confidence: 99%
“…By combining 5 study cohorts of 18 191 individuals, Lubitz et al 9 analyzed predictors of incident AF, as well as subsequent complications, such as stroke. They found that while a genetic risk score was associated with incident AF (maximum C statistic, 0.629-0.811), it added only marginally to clinical risk prediction (maximum ΔC statistic from clinical score alone, 0.009-0.017).…”
Section: Genetics Of Afmentioning
confidence: 99%